Electrochemical Reduction of Oxygen on Anthraquinone/Carbon Nanotubes Nanohybrid Modified Glassy Carbon Electrode in Neutral Medium - Zheng Gong; Guoquan Zhang; Song Wang (Journal of Chemistry)
The electrochemical behaviors of monohydroxy-anthraquinone/multiwall carbon nanotubes (MHAQ/MWCNTs) nanohybrid modified glassy carbon (MHAQ/MWCNTs/GC) electrodes in neutral medium were investigated; also reported was their application in the electrocatalysis of oxygen reduction reaction (ORR). The resulting MHAQ/MWCNTs nanohybrid was characterized by scanning electron microscope (SEM) and transmission electron microscope (TEM). It was found that the ORR at the MHAQ/MWCNTs/GC electrode occurs irreversibly at a potential about 214 mV less negative than at a bare GC electrode in pH 7.0 buffer solution. Cyclic voltammetric and rotating disk electrode (RDE) techniques indicated that the MHAQ/MWCNTs nanohybrid has high electrocatalytic activity for the two-electron reduction of oxygen in the studied potential range. The kinetic parameters of ORR at the MHAQ/MWCNTs nanohybrid modified GC electrode were also determined by RDE and EIS techniques.